2017
DOI: 10.1111/mcn.12434
|View full text |Cite
|
Sign up to set email alerts
|

Individual, household, and community level risk factors of stunting in children younger than 5 years: Findings from a national surveillance system in Nepal

Abstract: Despite substantial reductions in recent years in Nepal, stunting prevalence in children younger than 5 years remains high and represents a leading public health concern. To identify factors contributing to the stunting burden, we report multilevel risk factors associated with stunting in 4,853 children aged 6-59 months in a nationally and agroecologically representative random sample from the first year of the Policy and Science for Health, Agriculture, and Nutrition Community Studies, a community-based obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 56 publications
8
53
0
1
Order By: Relevance
“…In India, maternal education was associated with stunting and household hunger was associated with anaemia. This is consistent with previous studies (Dorsey et al, 2017;Eicher-Miller, Mason, Weaver, McCabe, & Boushey, 2009). In Peru, caregivers' hand washing behaviour was associated with stunting, in line with evidence that sanitation and hygiene can help reduce the burden of stunting (Cumming & Cairncross, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…In India, maternal education was associated with stunting and household hunger was associated with anaemia. This is consistent with previous studies (Dorsey et al, 2017;Eicher-Miller, Mason, Weaver, McCabe, & Boushey, 2009). In Peru, caregivers' hand washing behaviour was associated with stunting, in line with evidence that sanitation and hygiene can help reduce the burden of stunting (Cumming & Cairncross, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…Mother and Fathers' higher education status is associated significantly with the less likelihood of child of less than five years being stunted (moderate and severe) in Punjab, Pakistan. This result is in line with other studies from Asia and Africa [57,34,58,59,28]. Although the channels through which education of parents can affect child health outcomes are debated as it hypothesized that higher educated parents are relatively better endowed with (health care) knowledge and resources, relatively rich and better able to provide childcare [60,28,61].…”
Section: Discussionsupporting
confidence: 88%
“…Another important WASH variable is access to safe drinking water but the methods for how the safe drinking water variable is defined and included in existing nutritional studies vary markedly. They mainly differ on either use of a protected water source [24,32], piped water source [11,33] or household water treatment methods [34][35][36]. In resource constraint settings where a water pipeline system is unreliable and not well maintained, the risk of water contamination in the supply chain remains high [16,37] potentially diluting the effect measure and strength of association.…”
Section: Exposure Variablesmentioning
confidence: 99%
“…The relative contribution of WASH interventions on childhood undernutrition is still unresolved in the current literature [21,22] with some studies providing conflicting results depending upon study design, nutritional outcomes and geographical settings where studies were conducted [11,[21][22][23]. Despite this, a majority of cross-sectional studies have consistently demonstrated a crucial role of improved WASH practices on childhood nutrition outcomes [6,11,24,25]. However, wide spread variation in methodological approaches and study settings have often posed a considerable challenge for interpretation and synthesis of study findings, limiting the prospect of providing definitive policy recommendations.…”
Section: Introductionmentioning
confidence: 99%